HUBUNGAN KADAR LEUKOSIT MONOSIT DAN PROKALSITONIN DENGAN KEJADIAN INFEKSI DAN LUARAN FUNGSIONAL PADA STROKE AKUT - Rivita Putri Nasari,* Aldy Safruddin Rambe,* Aida Fithrie* (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION INFECTION IS A COMMON COMPLICATION IN THE ACUTE OF STROKE STROKE CAN LEAD TO IMMEDIATE STAGE OF IMMUNOSUPPRESSION INCREASING THE RISK OF INFECTION